Microwave filters, impedance-matching networks, and coupling structures - Matthaei, George L.; Young, Leo; Jones, E. M. T. (Artech House, 1980)
The book details fundamental concepts, techniques, and data of general use in the design of a wide range of structures. In addition, specialized data is featured which makes it easy to work out practical, specific designs. Hundreds of equations, photos, and tables present the data you need at a glance. An indispensable engineering tool!.